Summary of Baseline Household Survey Results: Vaishali Site, Bihar State (Northeast India) - Bhatta, Gopal Datt; Singh, RKP; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This report summarizes the results of a household survey of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) carried out in the Vaishali sampling frame of Bihar, northeast India, with an objective to better understand the baseline characteristics of farm families, changes in farming practices over the last 10 years, household livelihood sources, and household food security and asset profiles, among others.